Sistem Pakar Diagnosis Dini Penyakit Lambung Menggunakan Metode Certainty Factor - Walangitan, Rafaely Hesky; Hasan, Patmawati; Tatuhey, Emy Lenora (STMIK Banjarbaru, 2024)
The diagnosis of gastric diseases at the Tanjung Ria Health Center often takes a lot of time and money for patients. Long queues and high consultation costs are the main obstacles, while medical personnel also face challenges in dealing with large patient volumes and limited working hours. The primary objective is to enhance the efficiency and accuracy of the diagnosis process, thereby assisting ordinary people in diagnosing gastric diseases. The development of an expert system based on certainty factors (CF) is necessary to enhance the diagnostic efficiency. This method will allow patients to get a quick and accurate diagnosis without having to wait for a long time or incur large costs. Testing with the black box method has confirmed the system's functionality in accordance with the expected specifications. The accuracy test result of 80% indicates that the system can generate a diagnosis in accordance with the expert's assessment.Keywords: Expert system; Certainty Factor (CF); diagnosis of gastric diseases; Tanjung Ria Health Center; accuracy testing. AbstrakDiagnosis penyakit lambung di Pusat Kesehatan Tanjung Ria seringkali membutuhkan banyak waktu dan uang bagi pasien. Barisan panjang dan biaya konsultasi yang tinggi adalah hambatan utama, sementara staf medis juga menghadapi tantangan dalam menangani volume pasien yang besar dan jam kerja yang terbatas. Tujuan utama adalah untuk meningkatkan efisiensi dan akurasi proses diagnostik, dengan demikian membantu orang biasa dalam mendiagnosis penyakit perut. Pengembangan sistem ahli berdasarkan faktor kepastian (Certainty Factor/ CF) diperlukan untuk meningkatkan efisiensi diagnostik. Metode ini akan memungkinkan pasien untuk mendapatkan diagnosis yang cepat dan akurat tanpa harus menunggu lama atau dikenakan biaya besar. Pengujian dengan metode kotak hitam telah mengkonfirmasi fungsionalitas sistem sesuai dengan spesifikasi yang diharapkan. Hasil tes akurasi 80% menunjukkan bahwa sistem dapat menghasilkan diagnosis sesuai dengan penilaian ahli.Kata kunci: Sistem pakar; Certainty Factor (CF); diagnosa penyakit lambung; Puskesmas Tanjung Ria; pengujian akurasi.